2008
DOI: 10.1093/chemse/bjn067
|View full text |Cite
|
Sign up to set email alerts
|

Methods of Human Body Odor Sampling: The Effect of Freezing

Abstract: Body odor sampling is an essential tool in human chemical ecology research. However, methodologies of individual studies vary widely in terms of sampling material, length of sampling, and sample processing. Although these differences might have a critical impact on results obtained, almost no studies test validity of current methods. Here, we focused on the effect of freezing samples between collection and use in experiments involving body odor perception. In 2 experiments, we tested whether axillary odors wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
97
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(99 citation statements)
references
References 49 publications
(65 reference statements)
0
97
2
Order By: Relevance
“…Cotton wool pads were taped with Micropore TM tape under both armpits after showering with non-perfumed soap, immediately before the men went to bed (see Roberts, Gosling, Carter, & Petrie, 2008;, and were worn in bed for 8-10 h. In the morning, the men placed the pads in plastic bags and delivered them to the laboratory where they were stored in a -80˚C freezer until testing, which occurred within 1 month of collection. Freezing does not qualitatively alter subsequent perception of odors (Lenochova, Roberts, & Havlicek, 2009;. Male participants were non-smokers, undertook to avoid using deodorants or aftershaves on the day of collection, and to refrain from consuming alcohol or certain strong-smelling foods, and from sexual activity during sample collection (for more details of such restrictions, see .…”
Section: Materials and Proceduresmentioning
confidence: 99%
“…Cotton wool pads were taped with Micropore TM tape under both armpits after showering with non-perfumed soap, immediately before the men went to bed (see Roberts, Gosling, Carter, & Petrie, 2008;, and were worn in bed for 8-10 h. In the morning, the men placed the pads in plastic bags and delivered them to the laboratory where they were stored in a -80˚C freezer until testing, which occurred within 1 month of collection. Freezing does not qualitatively alter subsequent perception of odors (Lenochova, Roberts, & Havlicek, 2009;. Male participants were non-smokers, undertook to avoid using deodorants or aftershaves on the day of collection, and to refrain from consuming alcohol or certain strong-smelling foods, and from sexual activity during sample collection (for more details of such restrictions, see .…”
Section: Materials and Proceduresmentioning
confidence: 99%
“…Previous studies have shown that freezing length over this time frame does not influence body odour quality (Roberts et al, 2008;Lenochova et al, 2009). …”
Section: Odour Sample Collectionmentioning
confidence: 82%
“…Also, the time interval between storage and the last defrosting was less than 6 months (Lenochova et al 2009). …”
Section: Sampling Of Donors' Body Odormentioning
confidence: 99%